Geographic distance and ecosystem size determine the distribution of smallest protists in lacustrine ecosystems. Issue 1 (18th March 2013) - Lepère, Cécile; Domaizon, Isabelle; Taïb, Najwa; Mangot, Jean‐François; Bronner, Gisèle; Boucher, Delphine; Debroas, Didier
Abstract Understanding the spatial distribution of aquatic microbial diversity and the underlying mechanisms causing differences in community composition is a challenging and central goal for ecologists. Recent insights into protistan diversity and ecology are increasing the debate over their spatial distribution. In this study, we investigate the importance of spatial and environmental factors in shaping the small protists community structure in lakes. We analyzed small protists community composition (beta‐diversity) and richness (alpha‐diversity) at regional scale by different molecular methods targeting the gene coding for 18S rRNA gene (T‐RFLP and 454 pyrosequencing). Our results show a distance–decay pattern for rare and dominant taxa and the spatial distribution of the latter followed the prediction of the island biogeography theory. Furthermore, geographic distances between lakes seem to be the main force shaping the protists community composition in the lakes studied here. Finally, the spatial distribution of protists was discussed at the global scale (11 worldwide distributed lakes) by comparing these results with those present in the public database. UniFrac analysis showed 18S rRNA gene OTUs compositions significantly different among most of lakes, and this difference does not seem to be related to the trophic status.